PENGARUH KOMUNIKASI INTERPERSONAL CUSTOMER SERVICE GO-JEK INDONESIA TERHADAP LOYALITAS PELANGGAN DI JABODETABEK - Rizky, Sarah Vania; Sharinta, Elviera Joelanda (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
Interpersonal communication is one important aspect for customer service in a company which engaged in services. This research was conducted to observe the influence of interpersonal communication of Go-Jek Indonesia’s customer service on customer loyalty in Jabodetabek and what other factors may come into play to achieve such result. The principle theory used in this research is the theory of interpersonal communication with customer loyalty as the supporting theory. The research method used is the quantitative explanative method, by distributing questionnaires to 100 respondents of Go-Jek Indonesia’s users who have contacted the customer service. This research uses the Likert scale as the measurement scale. From the results of research found the contribution of interpersonal communication of Go-Jek Indonesia’s customer service value equals to 37,3% on customer loyalty in Jabodetabek, with result of regression coefficient value equal to 0,552 and constant value equal to 32,444. Keywords: Interpersonal communication, customer service, customer loyalty